2006
DOI: 10.1111/j.1365-3059.2006.01361.x
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between leaf emergence and optimum spray timing for leaf blotch (Rhynchosporium secalis) control on winter barley

Abstract: For wheat, the optimum time to apply fungicide to control disease on a given leaf layer is usually at, or shortly after, full leaf emergence. Data from field experiments on barley were used to investigate whether the same relationship was applicable to control of leaf blotch on barley. Replicated plots of winter barley were sown in the autumns of 1991, 1992 and 1993 at sites in southwest England with high risk of Rhynchosporium secalis infection. Single fungicide treatments at four doses (0·25, 0·5, 0·75 or 1·… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 22 publications
(35 reference statements)
0
2
0
Order By: Relevance
“…These results are consistent with other UK published results. For example, Gladders and Hims22 and Young et al 23 found that fungicide spraying can increase winter barley yields by about 1 t ha −1 .…”
Section: Resultsmentioning
confidence: 68%
“…These results are consistent with other UK published results. For example, Gladders and Hims22 and Young et al 23 found that fungicide spraying can increase winter barley yields by about 1 t ha −1 .…”
Section: Resultsmentioning
confidence: 68%
“…Foliar fungicides are used on most barley crops in Europe. In winter barley crops, fungicides applied in the early spring at GS25‐30 can greatly decrease disease development and therefore increase yield, but the best fungicide timing is generally at GS31‐32 (Young et al ., 2006). In spring barley crops, fungicide treatments are generally recommended where the disease is found on the upper three leaves of a susceptible cultivar.…”
Section: Integrating Strategies For Control Of Rhynchosporium Includmentioning
confidence: 99%